O blog como instrumentação para professor de ciências das séries iniciais - Galvão, Giovani Fernandes (2012)
The increasing presence of technology in educational environments creates new pedagogical needs. On the other hand, teachers do not receive or have not received adequate training to include these technologies in their practices, and they are not so well placed in a cybercultural context as their students who are increasingly born with ease for interactions in cyberspace. In this context it is envisioned this study that was realized with a teacher from a municipal school in the city of Ponta Grossa, Paraná, with the goal of produce a blog with basic information and suggestions for tools to use in the Early Grades of Science Teaching through which she could catch up technologically to improve their teaching practices in cyberspace and interact with their students and other education professionals. The content of the research product was basically matters on computing, operating systems, network security, media files, free software and freeware for their use in updating the teacher in relation to the Information and Communication Technologies for science classes in elementary school. The research methodology was the Interventional Research, which gives to the study some flexibility that was needed for the knowledge construction as required to the teacher and to the served community. The qualitative data collection was to evaluate which issues were most needed to the teacher and for the physical and virtual interactions between her and the researcher, which issues had higher utilization. The approach used was mentorial, given the circumstances of virtual and personal relationship in which interactions occurred between researcher and teacher. In view of the issues surrounding this study, the literature review includes questions related to Cyberculture in teacher education, previous works in teacher’s formation in relation to this activity and official documents that guide the Science Teaching for the early grades as well as their relationships with the teaching. After the interactions between researcher and teacher, interventional research subjects, it was observed the construction of a blog as a form of auxiliary reference to work with the Information Technology and Communication both in the classroom and in their continuing education.